Paradigma Teologi Injili Mengenai Pendayagunaan Matra-Matra Budaya Dalam Pekabaran Injil Kontekstual - Marde Christian Stenly Mawikere; Sudiria Hura (Peneliti.net, 2022)
This article is a conceptual study of cultural elements and contextual evangelism approache according to the paradigm of Evangelical Christians. The research was conducted using a descriptive method built on relevant literature research (or documentary analysis). This study begins with conducting research on the dynamics of theological perception of the gospel and culture. Then proceed with the understanding of culture and cultural dimensions and their correlations which are important to determine the use of these dimensions in a contextual evangelistic approach. The final result of this study shows that the attention to culture in developing contextual evangelism approaches does not mean that the church has to fully adapt or assume there is a harmony between the gospel and culture. Precisely by understanding and utilizing cultural elements in contextual evangelism, it will appear that the gospel has an advantage with regard to the assurance of eternal salvation in the Lord Jesus Christ. Therefore, efforts to prepare a contextual evangelist who has integrity, character, and competence regarding the Bible and culture is very important.